Powered Respirators Are Effective, Sustainable, and Cost-Effective Personal Protective Equipment for SARS-CoV-2 - Alasdair Munro; Alasdair Munro; Jacqui Prieto; Jacqui Prieto; Emmanouil Mentzakis; Mohammed Dibas; Nitin Mahobia; Peter Baker; Sarah Herbert; Trevor Smith; Matthew Hine; Joann Hall; et al. (Frontiers in Medical Technology, 2021)
Objectives: The provision of high-quality personal protective equipment (PPE) has been a critical challenge during the COVID-19 pandemic. We evaluated an alternative strategy, mass deployment of a powered air-purifying respirator (PeRSo), in a large university hospital.Methods: We performed prospective user feedback via questionnaires sent to healthcare workers (HCWs) issued PeRSos, economic analysis, and evaluated the real-world impact.Results: Where paired responses were available, PeRSo was preferred over droplet precautions for comfort, patient response, overall experience, and subjective feeling of safety. For all responses, more participants reported the overall experience being rated “Very good” more frequently for PeRSo. The primary limitation identified was impairment of hearing. Economic simulation exercises revealed that the adoption of PeRSo within ICU is associated with net cost savings in the majority of scenarios and savings increased progressively with greater ITU occupancy. In evaluation during the second UK wave, over 3,600 respirators were deployed, all requested by staff, which were associated with a low staff absence relative to most comparator hospitals.Conclusions: Health services should consider a widespread implementation of powered reusable respirators as a safe and sustainable solution for the protection of HCWs as SARS-CoV-2 becomes an endemic viral illness.